Institutional Arrangement of Regional Apparatus in Kulon Progo Regency Government, Indonesia - Agung Kurniawan; Dyah Mutiarin (Journal of Governance and Public Policy, 2024)
The Kulon Progo Regency Government, Special Region of Yogyakarta, experienced a significant decrease in the number of employees from 2014 to 2019. This is due to the number of State Civil Apparatus who reached the retirement age limit and made outgoing mutations far more than the number of state civil apparatus received through the State Civil Apparatus Candidate recruitment route and mutations that entered the region. In fact, the number of Kulon Progo State Civil Apparatus is the lowest when compared to other districts in Yogyakarta. Therefore, this study aims to determine the institutional arrangement of the Kulon Progo regional apparatus and the factors that influence it. This research uses a qualitative descriptive method, namely by describing clearly and in depth the information obtained and then systematically compiling the findings of    the findings from the results of the study. Data, information, and research findings are then summarized in such a way as to provide conclusions related to the object of research.  The results show that the institutional arrangement of the regional apparatus of Kulon Progo Regency is fairly good. This is due to the existence of strong and clear regulations, the availability of qualified and competent human resources, and the bureaucratic reform measures that are being implemented. Nevertheless, there are still obstacles faced, namely constraints in providing guidance to functional positions.